Strategi Pengajaran Moderasi Beragama untuk Mengurangi Intoleransi di SMA - Hilma Suciani Az zahra; Muhamad Wildan Al azhari; Anita Hasanah; Asti Hildawati; Fiqra Muhamad Nazib (Yayasan Al-Afif, 2025)
This research aims to design strategies for teaching religious moderation at the high school level as a measure to address intolerance among students. In the context of Indonesia, which is rich in religious and cultural diversity, religious moderation plays a crucial role in fostering social harmony. The method used in this study is a Systematic Literature Review, gathering various references from journal sources. The results show that teaching religious moderation through interactive approaches, instilling values of tolerance, and experiential learning can deepen students' understanding of the importance of interfaith harmony. Furthermore, approaches that emphasize religious pluralism and appreciation for differences have proven effective in reducing the potential for intolerance. This study recommends implementing structured and integrated religious moderation teaching strategies into the high school curriculum to strengthen social integration and create a more inclusive school environment.